The Effect of Integrated Turkish and Science Activities in Pre-School Education on Children's Environmental Perception - Çağlar, Atila (Kastamonu Egitim Dergisi, 2024)
Purpose of the Study: The purpose of this study is to determine the effect of integrated Turkish and science activities in the preschool period on children's environmental perception. Materials and Methods: A mixed-method approach was used in the research. In the qualitative dimension of the mixed method, a phenomenological design was employed, while in the quantitative dimension, a quasi-experimental design was used. The sample of the study consists of 20 children, with 10 children in the experimental group and 10 children in the control group. As the first stage of the experimental procedure, children in both the experimental and control groups were asked to draw an environment picture, and one-on-one interviews were conducted with the children regarding their drawings. The drawings were evaluated using a Draw An Environment Test-Rubric (DAET-R) and were attempted to be transformed into qualitative form with yellow and blue color tones. Additionally, the children's rubric scores were transferred to the SPSS 23 package program, and necessary analyses were conducted. In the implementation part of the study, nine integrated Turkish and science activities were applied to the experimental group over a period of nine weeks. A different illustrated children's book was used in each activity, and the activities were developed within the framework of these books. The control group, on the other hand, continued with the daily educational routines included in the preschool education program. As the final stage of the experimental part, children in both the experimental and control groups were asked to draw another environment picture, and one-on-one interviews were conducted with the children regarding their drawings. Findings: In the final tests of the experimental group, there was an increase in figures related to the environment in the drawings. It was found that the final test drawings of the children in the experimental group were related to the illustrated books used in the integrated activities. Significant differences were detected in the final tests of the experimental and control groups through statistical tests. Key Points: As a result of the study, it was determined that the change in environmental perception of the children in the experimental group, where integrated Turkish and science activities developed with illustrated children's books were applied, progressed more prominently compared to the children in the control group.
Keywords: 4. Education; 3. Good health